Revitalisasi Terminal Penumpang Tipe A (Studi Kasus : Terminal Regional Daya Kota Makassar) - RAHMI, A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Revitalization of Terminal Regional Daya is one of the efforts to optimize the function and role of the terminal as a road transport network node that aims to drive efficiency Makassar society through physical intervention terminals are packed in a good layout, clean, comfortable, safe, and informative with management support and neat information system, so that the public interest would be to use the terminal as a transfer facility mode. This research aims to analyze the performance of Regional Daya station, to evaluate the operational performance of Terminal Regional Daya, and formulate the concept of proper design approach in order to revitalize Terminal Regional Daya. The research method used is descriptive qualitative and quantitative emphasis on empirical and theoretical study analyzed qualitatively with the normative approach/standard type A passenger terminal planning through the formulation of the concept of the design approach. The results showed that a decline in the function of Terminal Regional Daya caused by several factors, namely : the accessibility of the system is characterized by a low terminal location far from the city center without the support of the overall transportation system, system/mechanism is not professional because the terminal operations are not supported by Human Resources (HR) has a technical qualification in terms of competence of the management terminal, both in terms of educational qualifications or areas of ground transportation experience in the field of Road Transport Traffic (LLAJ), as well as the condition of the terminals facilities unfavorable movement mechanisms terminal users, either in terms of facility layout design system, circulatory system, ambiguity function facilities, and lack of information systems, signs, night lighting, and vegetation.